Neurostructural associations with traumatic experiences during child- and adulthood - Siehl, Sebastian; Sicorello, Maurizio; Herzog, Julia; Nees, Frauke; Kleindienst, Nikolaus; Bohus, Martin; Müller-Engelmann, Meike; Steil, Regina; Priebe, Kathlen; Schmahl, Christian; Flor, Herta (Translational Psychiatry, 2022)
Adverse experiences can lead to severe mental health problems, such as posttraumatic stress disorder (PTSD), throughout the lifespan. In individuals with PTSD, both global and local brain volume reductions have been reported—especially in the amygdala and hippocampus—while the literature on childhood maltreatment suggests a strong dependency on the timing of adverse events. In the present study, we pooled data from two studies to contrast the effects of reported trauma exposure during neurodevelopmentally sensitive periods in early life with trauma exposure during adulthood. A total of 155 women were allocated into one of six age-matched groups according to the timing of traumatization (childhood vs adulthood) and psychopathology (PTSD vs trauma-exposed healthy vs trauma-naïve healthy). Volumes of the amygdala and hippocampus were compared between these groups. Six additional exploratory regions of interest (ROI) were included based on a recent meta-analysis. Amygdala volume was strongly dependent on the timing of traumatization: Smaller amygdala volumes were observed in participants with childhood trauma and PTSD compared to the healthy control groups. In contrast, larger amygdala volumes were observed in both groups with trauma exposure during adulthood compared to the trauma-naïve control group. Hippocampal volume comparisons revealed no statistically significant differences, although the descriptive pattern was similar to that found for the amygdala. The remaining exploratory ROIs showed significant group effects, but no timing effects. The timing might be an important moderator for adversity effects on amygdala volume, potentially reflecting neurodevelopmental factors. Albeit confounded by characteristics like trauma type and multiplicity, these findings pertain to typical childhood and adulthood trauma as often observed in clinical practice and speak against a simple association between traumatic stress and amygdala volume.